Analysis of a potential coalburst phenomenon in different strata layers in underground coal mines - Zhang, C.; Canbulat, I.; Tahmasebinia, F.; Vardar, O.; Saydam, S. (Deep Mining 2017: Proceedings of the Eighth International Conference on Deep and High Stress Mining, 2017)
Coalburst is referred to as the violent failure of overstressed coal, which has been recognised as one of the most critical dynamic failures in coal mines. This paper aims to analytically and numerically evaluate the energy transformation between the different strata and coal layers. An accurate closed-form solution is developed. Due to the complexity of the causes and mechanisms contributing to the coalburst occurrence, 3D finite element modelling was developed to validate the suggested analytical assessments of rock/coalburst occurrence. The energy concept is emphasised in order to improve the understanding of the underlying mechanisms of coalburst. Only with enhanced understanding of the driving mechanisms, a reliable coalburst risk assessment can be achieved.